نسبة انتشار شقوق الشفة وقبة الحنك في المنطقة الساحلية السورية - أسعد, منذر; قبيلي, عبد الجواد; حمود, لمى نديم (Latakia University Journal -Medical Sciences Series, 2019)
الهدف: يهدف البحث لتحديد نسبة انتشار شقوق الشفة وقبة الحنك في المنطقة الساحلية كأحد أهم التشوهات الخلقية التي تصيب الأطفال. المواد والطرق: لتحديد هذه النسبة, أجرينا دراسة استرجاعية لأضابير المواليد المصابون بشقوق الشفة وقبة الحنك في مشفى التوليد والأطفال في اللاذقية ومشفى التوليد في طرطوس خلال الأعوام من 2017-2012. النتائج: كانت نسبة انتشار هذه الشقوق في كل من اللاذقية وطرطوس 1:904. 47% من الشقوق هو CLP و 19% كان CP و 34% هو CL . تأثر الجانب الأيسر من الوجه حوالي- -2 مرة من الجانب الأيمن. نسبة إصابة الذكور بـ CLP 1.5 أكثر من الإناث. CP أكثر شيوعاً عند الاناث (70%) من الذكور (30%). الاستنتاجات والتوصيات: أظهرت نتائج هذه الدراسة الإحصائية ارتفاع في هذه الاصابات والتي تتطلب اتخاذ كافة الإجراءات اللازمة لإجراء الأرشفة للمولودين المصابين بهذا التشوه. Objective: The study aims to determine the prevalence of cleft lip and palate in the coastal area as one of the most important congenital malformations in children. Materials and methods: To determine this percentage, we conducted a retrospective study of neonatal tracts with cleft lip and palate in the obstetric and pediatric hospital in Lattakia and the obstetric hospital in Tartous during the years 2012-2017. Results: The prevalence of these clefts in both Lattakia and Tartous was1:904. 47 % of the patients had a cleft lip and palate (CLP), 19% of the patients had a cleft palate (CP), and 34% of the patients had a cleft lip (CL). The left side was affected 2 times more frequently than the right side. Boys had a CLP nearly 1.5 times more often than girls. CP was more common for girls (70%) than for boys (30%). Conclusion: The results of this study showed increase in the prevalence of these Clefts. Therefore, we demand that all necessary procedures be taken for the archiving of the newborns who suffer from this deformity.